Comparative of the Effectiveness and Safety of Biological Agents, Tofacitinib, and Fecal Microbiota Transplantation in Ulcerative Colitis: Systematic Review and Network Meta-Analysis. (19th May 2021) - Zhou, Hao-Yue; Guo, Biao; Lufumpa, Eniya; Li, Xiao-Mei; Chen, Li-Hong; Meng, Xiang; Li, Bao-Zhu
ABSTRACT: Background: Biological agents are commonly used for the treatment of ulcerative colitis (UC). As new treatments, tofacitinib, and fecal microbiota transplantation (FMT) have demonstrated efficacy in treating UC. This network meta-analysis aims to determine the efficacy and safety of biological agents, tofacitinib, and FMT. Methods: A network meta-analysis was conducted by systematically searching the PubMed, Embase, and Cochrane Libraries. According to strict inclusion and exclusion criteria, we included randomized controlled trials (RCTs) of biological agents, tofacitinib, and FMT in UC. A random-effect model was chosen by the network meta-analysis and sensitivity analysis. Heterogeneity test and publication bias test were performed to determine the efficacy of treatments. Results: Data were extracted from 16 RCTs and we found that all treatments were more effective than the placebos. A total of 21 comparisons were made to determine efficiency. We found that infliximab, vedolizumab, and FMT performed better curative effect in terms of absolute effects and relative ranks. Furthermore, there was no statistical difference in the efficacy of biological agents, tofacitinib, and FMT. Moreover, no treatments were found to increase the occurrence of adverse events when compared with placebos, except infliximab. However, vedolizumab seemed to reduce the occurrence of adverse events compared with infliximab. Conclusion: Of the biological agents, vedolizumab and infliximab were the most effective, suggesting that biological agents are still a better choice. Nevertheless, tofacitinib and FMT may be promising alternatives with high efficacies. However, more safety and maintenance studies need to be conducted in future for the acquisition of more accurate results. Abbreviations: FMT: Fecal microbiota transplantation; UC: Ulcerative colitis; RCTs: Randomized controlled trials; IBD: Inflammatory bowel disease; CD: Crohn's disease; IBS: Irritable bowel syndrome; CDI: Clostridium difficile infections; ITT: Intention-to-treat; RR : Relative risk; CI : Confidence interval; CrI : Credible intervals; IFX: Infliximab; ADA: Adalimumab; TFB: Tofacitinib; GLM: Golimumab; VDZ: Vedolizumab; PBO: Placebo; wk: week; F: Female; M: Male; AEs: Adverse events; SAEs: Serious adverse events; anti-TNF: Anti-tumor necrosis factors